PELAYANAN PUBLIK DI KANTOR IMIGRASI BLITAR - Ernanda, Rizki Fajar (Universitas Kadiri, 2019)
The purpose of this study was to describe and analyze Public Services at the Blitar Immigration office as well as factors that support and inhibit public services at the Blitar Immigration Office. To answer the research objectives in measuring through the Quality of Service Outcomes, Accuracy in Service, Timeliness in Service, Courtesy and Employee Friendliness in Service and Justice in Service This research is a qualitative descriptive type, with the location of the study at the Blitar Immigration Office. Primary data came from interviews with five selected informants and also from direct observations at the study site. While secondary data comes from information or data owned by agencies. Withdrawal of conclusions based on data processed using interactive model analysis. From the results of the study, it can be concluded that public services at the Blitar Immigration Office are good but not optimal. The quality of the effects of public services has been carried out in accordance with procedures and full of accuracy so that there are minimal errors; Timeliness of the completion of public services in accordance with the regulation, which is a maximum of 4 working days; Service by officers is carried out politely and full of hospitality Justice in service is carried out through queuing methods so that it does not cause conflict between the applicant and gives more certainty; Justice in Service has been carried out using the queue method so that it does not create conflict between applicants. The factors that support public services at the Blitar Immigration office are the availability of adequate facilities and infrastructure, while the inhibiting factors are the lack of staff and network problems.